Endovascular Treatment for Acute Ischemic Stroke in China: a study protocol for a prospective, national, multi-center, registry study - Liu, Liang; Nguyen, Thanh N.; Chen, Hui-Sheng (Frontiers in Neurology, 2023)
Background: Endovascular treatment (EVT) is the standard treatment for acute ischemic stroke (AIS) patients with large vessel occlusion (LVO).: Endovascular Treatment for Acute Ischemic Stroke in China (DETECT2-China) aims to evaluate real-world outcomes and safety of EVT for LVO-AIS patients in China. Design: DETECT2-China is a prospective, national, multi-center study registered in ClinicalTrials.gov (NCT05092139). This study plans to enroll a total of 3000 consecutive patients who received EVT for LVO. All eligible patients are adults aged 18 years or older with acute LVO who received EVT and standard medical treatment according to the Chinese stroke guidelines and local practice. Outcome: The primary outcome is functional independence (modified Rankin Scale score, mRS ≤2) at 90 days. The secondary outcomes include: (1) proportion of patients with mRS 0 to 1 at 90 days, (2) distribution of mRS at 90 days, (3) changes in National Institutes of Health stroke scale (NIHSS) at 24 hours, 48 hours, and 12 days or discharge (whichever is earlier), (4) proportion of symptomatic intracranial hemorrhage (sICH) within 48 hours, (5) proportion of death within 7 days. Discussion: The DETECT2-China will provide real-world data about the effectiveness and safety of EVT for AIS-LVO patients in China.